2019
DOI: 10.1111/pce.13675
|View full text |Cite
|
Sign up to set email alerts
|

Seminal roots of wild and cultivated barley differentially respond to osmotic stress in gene expression, suberization, and hydraulic conductivity

Abstract: Wild barley, Hordeum vulgare spp. spontaneum, has a wider genetic diversity than its cultivated progeny, Hordeum vulgare spp. vulgare. Osmotic stress leads to a series of different responses in wild barley seminal roots, ranging from no changes in suberization to enhanced endodermal suberization of certain zones and the formation of a suberized exodermis, which was not observed in the modern cultivars studied so far. Further, as a response to osmotic stress, the hydraulic conductivity of roots was not affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 74 publications
6
46
1
Order By: Relevance
“…In addition, it is widely known that root is the major organ to respond to osmotic stress caused by drought and salt [43]. In this study, MdNF-YA6, MdNF-YA9, MdNF-YB8, MdNF-YB9, MdNF-YB18, MdNF-YB19, MdNF-YC7, and MdNF-YC8 are mainly or specifically expressed in roots (Figure 8).…”
Section: Function Of Mdnf-y Genes In Abiotic Stressmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, it is widely known that root is the major organ to respond to osmotic stress caused by drought and salt [43]. In this study, MdNF-YA6, MdNF-YA9, MdNF-YB8, MdNF-YB9, MdNF-YB18, MdNF-YB19, MdNF-YC7, and MdNF-YC8 are mainly or specifically expressed in roots (Figure 8).…”
Section: Function Of Mdnf-y Genes In Abiotic Stressmentioning
confidence: 69%
“…The specific cis-element analysis of the MdNF-Y genes is shown in Table S5. Actually, some reports in other plants have indicated that NF-Ys participated in response to abiotic stresses (cold [42], heat [25], drought [43], and salinity [28], root development [44], seed-specific regulation [44] and photoperiod-dependent flowering [29]. So, we further detected the expression levels of Figure 6.…”
Section: The Cis-acting Regulatory Members In the Promoter Of Mdnf-y mentioning
confidence: 91%
“…Furthermore, addition of salt to the root medium of plants grown under control conditions results in a turgor change in leaf cells which is equivalent to a root σ of 1.11 (for details, see File S1 and compare Fricke, 1997). We do not know why work on other barley cultivars has yielded values for σ as low as 0.29–0.61 using the root pressure probe (Kreszies et al, 2019, 2020; Ranathunge et al, 2017). One basic difference between these and this study is that the other studies used a 4–5 cm long tip segment of the root, whereas we used an entire root (typically 12–15 cm long), which includes the basal, fully mature portion with all the lateral roots and reflects more the situation in the plant.…”
Section: Discussionmentioning
confidence: 95%
“…Despite these uncertainties, the data suggest that we do not necessarily need a low‐conducting endodermis to explain the decrease in root‐Lp in response to salt—nor do we need one to explain the root‐Lp in control plants (Figure 9b). This does not mean that an endodermis with a particularly low conductance to water does not exist; neither does it question results on other plants species or for other experimental treatments where suberin lamellae have been implicated in the hydraulic response of roots (Armand et al, 2019; Gitto & Fricke, 2018; Kreszies et al, 2019, 2020). Maturation of apoplastic barriers closer to the tip under salt stress, as observed here and reported previously (Azaizeh & Steudle, 1991; for discussion, see Byrt et al, 2018) does not need to contribute to the reduction in Lp of entire root system and may mainly restrict the entry of Na + and Cl‐ into the stele.…”
Section: Discussionmentioning
confidence: 97%
“…The increased basal level in suberin deposition at the endodermis in UCB1 suggests an early energy investment in enforcing salt exclusion from the vascular cylinder, and that this mechanism is more strongly utilized by UCB1 under salinity stress. Selection pressure for crop varieties with increased apoplastic barriers suberization has been shown for barley (Kreszies et al, 2020), suggesting that this energy investment is preferred in monocots. The popularity of UCB1 in pistachio breeding indicates a similar trend is taking place in woody perennial nut crops.…”
Section: A Root Developmental Gradient In Vacuolar Sequestrationmentioning
confidence: 99%